Enhanced Deglacial Carbon Transport by Pacific Southern-Sourced Intermediate and Mode Water - Karas, C (Nature Research, 2025)
Southern-sourced Antarctic Intermediate Water (AAIW) and Subantarctic Mode Water (SAMW) are currently major sinks of atmospheric CO2. During the last deglaciation, atmospheric CO2 levels increased significantly during two specific time periods, Heinrich Stadial 1 (H1) ~18–14.6 ka BP (thousand years ago before present) and the Younger Dryas (YD) ~12.8–11.5 ka BP. Model simulation and proxy data studies suggest that AAIW/SAMW was crucial in explaining these changes during H1 and YD, but its variability and properties in the Southeast Pacific Ocean are still largely unknown. Here, we present records of benthic foraminiferal carbon isotopes, Mg/Ca-based water temperatures, paleosalinity reconstructions, and sortable silt mean grain size variations over the last 30 thousand years from Ocean Drilling Program (ODP) Site 1233, in the Southeast Pacific Ocean, which is bathed in AAIW/SAMW. Our proxy data suggest an increased northward circulation of high pCO2/ nutrient-enriched AAIW/SAMW during H1 and YD. Our data provides support for AAIW/SAMW as one of the important conduits for deglacial oceanic outgassing in the eastern equatorial Pacific upwelling. © The Author(s) 2025.